Elaboración de un plan de marketing para el producto café victoria amazónico orgánico de la empresa Fapecafes para la ciudad de Zamora - Guarinda Rosillo, Gilber Alexi (2016)
Marketing analyzes the commercial management of the business in order to attract, retain and engage customers through satisfying their needs, often focus their activities throughout the 4 Ps: Product, Price, Place (distribution) and advertising (promotion). The investigation work we perform with the approach of a problem, although the product is of high quality, has internationally certified Fair Trade - FLO International (Fair Trade Labelling Organization) and Organic Certification BSC, despite being a product of unable to export position in local markets, however it is necessary to address these markets as their knowledge of them is void due to lack of publicity. As a general objective, larger marketing victory Amazon and publicize coffee production in Southern Amazonia internationally certified Fair Trade and Organic Certification and specific objectives; Diagnose Business Object Studio, Performing a proposal for a Strategic Marketing Plan for Victoria Cafe Amazon product. Several objectives which comprises preparing the marketing plan that will achieve the same higher positioning of both the company and the product market within the City of Zamora was raised. To carry out the research work the following methodology was used: Analytical Method; through situational analysis it gave a clearer picture of the current situation of the company and provide the opportunity to submit 7 proposals for solutions to possible problems. The Deductive Method, for the problem statement and the theoretical framework. The inductive method, the outcomes approach as external factors or Macro environment (opportunities and threats) in different areas such as Socio- Cultural, Technological, Economic, Competitive, Political, Legal, and Porter’s five forces analysis of each variables in their relationship with the company and its environment , as in the conclusions and recommendations. The Statistical Method for fieldwork in surveys and interviews to collect, analyze and interpret numerical and statistical data. The techniques used were the interview applied to company president “FAPECAFES “the survey (9 employees) and 354 surveys of the inhabitants of the city of Zamora. A SWOT analysis of the company the same containing Strengths occurred; own infrastructure , feature collection centers at strategic locations It has a processing plant specialty coffees : trite , classification, separation defects , according to customer's requirement , There is a management team to focus on exports , is there an export quality product , the product has international certifications. Opportunities, increase of new members - producers, Harnessing the positioning of the organization for growing specialty coffee sales services special collection and conventional coffees , Learning lessons having FAPECAFES to provide marketing and production of specialty coffees, develop and therefore advertising client extension . Weaknesses ; Lack of commitment from partners for the 8 delivery of coffee, not made promotions and advertising is null , Lack of a marketing plan , personal foul specialized in sales. Threats, Prices in New York bag with downward trend, competition with better technologies, price instability. A proposal was made in order to improve the operation of the Company consisting of the same three objectives: The first "Design an Advertising Plan" that it will cost $ 5,184.50 the second objective, is $2400 "Designing a Plan promotions. “And the third objective is," Develop a Plan for Personal Training Business Sales FAPECAFES "taking an $3202.40, all having a total budget of $ 10786.90 Finally it came to determining the Conclusions, The Company lacks an advertising plan that allows you to know both its organizational structure and its products, because the advertising they do is null, the company lacks a plan promotions that allow motivate customers for their purchase, lack of a sales training plan staff in that department charged. and Recommendations ; Apply long term that allows the company to be more known where customers identify with it and choose to purchase their products, constant promotions and discounts Apply product to motivate the client by purchasing an advertising plan who is the main body for the survival of a business or organization , you train more often employees not only in the sales department , but the entire staff working in different departments , who will let you have a trained staff ideas new order to be more efficient and effective when performing their duties.